Про політичні партії як державно-правовий інститут - Наливайко, Т. В.; Nalyvajko, T. V. (Ужгородський національний університет, 2012)
Розглянуто окремі теоретико-правові аспекти інституту політичних партій: відображення в Конституції України, витоки феномену, сучасний статус, інші проблемні питання (механізм реалізації інтересів регіональних груп, протиріччя щодо формування й участі у виборах тощо). The article deals with consider some theoretical and legal aspects of the Institute of Political Parties: according to the Constitution of Ukraine, the origins of the phenomenon, present status and other issues (the mechanism of the interests of regional groups, inconsistencies in the formation and participation in elections, etc.).
On political parties as public-legal institution
Keywords: політична система; політична партія; державно-правовий інститут; political system; political party; public-law institution